Perbaikan Kualitas Layanan dengan Pendekatan Servqual dan Importance Performance Analysis - Rahman Manurung; Supriyadi Supriyadi; Tri Joko Wibowo (Universitas Serang Raya, 2016)
Customer satisfaction in the service sector is an important and decisive element in developing the company so that it still exists in the face of competition. Improving service to consumers is very important in an effort to increase customer satisfaction. The problems faced by companies today are inefficiencies in the service process caused by the amount of waste and non-value added activities that can harm the company, such as handling damage to slow piping, frequent complaints from customers, thus impacting consumer satisfaction. This study aims to identify the expectations or desires of consumers, the level of customer satisfaction with the quality of services and propose improvements to service quality based on priority improvements from the IPA diagram. This study, using questionnaires, interviews and observations in data collection. Research respondents were all representatives of consumers totaling 10 companies. Survey results are processed using validity and reliability, Servqual and Importance Performance Analysis (IPA) tests. The results showed that the level of customer satisfaction with the average service quality was still unsatisfactory. This is evidenced by the results of a negative gap obtained from all dimensions measured. To improve the quality of service can be done by fostering communication with the supplier (Pertamina) to make a special pipeline so that the flow of gas from the supplier is not divided with other distributors, making automatic control valve from the supplier, doing regular service, cooperation with other suppliers to back up gas when the supply from the main supplier is disrupted, and provides compensation for gas supply to consumers who experience gas supply shortages